Pengaruh Kompensasi Terhadap Kinerja Karyawan pada Koperasi Jaya Abadi - Jintar, Catry; Paramita, Bunga (Bahtera Inovasi, 2022)
Human resources have a major role in an organization or company. All aspects related to human resources in the end also affect performance, especially in relation to employee performance, in this study the authors focus on Employee Compensation and Performance. This study aims to determine empirically the effect of compensation on employee performance at the Jaya Abadi Cooperative. This study uses a population and a sample of 30 employees as respondents. The data collection technique used an online questionnaire with a google form that was sent to the respondents. The data obtained were analyzed using simple linear regression analysis. The results obtained indicate a real and significant effect of compensation variables on employee performance.